Kabbalistische Sagen - Bloch, Chajim 1881-1973; Lurya, Yitsḥaḳ ben Shelomoh 1534-1572 (Leipzig Verl. d. Asia Major, 1925)
Legenden um Yiṣḥāq Luria
Archivierung/Langzeitarchivierung gewährleistet
Archivierung/Langzeitarchivierung gewährleistet